The image, medium and objective in the painter of battles of Arturo Perez Reverte - Virginia Isla García (Corporación Universitaria Minuto de Dios, 2009)
The essay's purpose is to contemplate the relationship between the image (as an experience and as a memory) as well as its role and exposure in El pintor de batallas', a story written by Arturo Pérez-Reverte (2006). Supporting our statements in the text, we will deduce this relationship to have as the main consequences the assumed limits of the space and time, as well as the creation, with the resources and constructions of the fiction, of a fragmented and subjective image that the reader will need to rebuild to better perceive the universality the novel aims at.